Optimum Design and Operation of an HVAC Cooling Tower for Energy and Water Conservation - Clemente García Cutillas; Javier Ruiz Ramírez; Manuel Lucas Miralles (Energies, 2017)
The energy consumption increase in the last few years has contributed to developing energy efficiency policies in many countries, the main goal of which is decreasing CO 2 emissions. One of the reasons for this increment has been caused by the use of air conditioning systems due to new comfort standards. In that regard, cooling towers and evaporative condensers are presented as efficient devices that operate with low-level water temperature. Moreover, the energy consumption and the cost of the equipment are lower than other systems like air condensers at the same operation conditions. This work models an air conditioning system in TRNSYS software, the main elements if which are a cooling tower, a water-water chiller and a reference building. The cooling tower model is validated using experimental data in a pilot plant. The main objective is to implement an optimizing control strategy in order to reduce both energy and water consumption. Furthermore a comparison between three typical methods of capacity control is carried out. Additionally, different cooling tower configurations are assessed, involving six drift eliminators and two water distribution systems. Results show the influence of optimizing the control strategy and cooling tower configuration, with a maximum energy savings of 10.8% per story and a reduction of 4.8% in water consumption.